Secuenciamiento de cepas de levaduras nativas con elevada capacidad de producción de biodiesel - Sosa Becerra, Roxana Beatriz (2020)
An alternative to the use of vegetable oils for the biodiesel production is the use of oleaginous yeasts, that have the capacity of accumulating amounts of cellular lipids greater than 20% of its biomass, mainly composed of triacylglycerols (TAG) rich in unsaturated fatty acids similar to soybean and rapeseed oil. The purpose of this research was the genome sequencing of two yeast strains with high biodiesel production capacity: Rhodotorula glutinis CON-5, Rhodotorula kratochvilovae POR-3, was performed. The biomass production for DNA extraction was made in YPD medium (30 ° C / 150 rpm / 48 hours). Then, the genomic DNA was extracted with DNAeasy soil Genomic DNA extraction kit and its quality and concentration was determined by agarose gel electrophoresis and microspectrophotometry using Nanodrop 2000c. Good quality genomic DNA samples were sequenced using Illumina technology and the Miseq equipment, with 300 bp pair-end reads. After that, the data preprocessing was carried out, which consists in determining the quality of the sequences obtained with the FastQC software, and then the low quality sequences were trimming using the FASTP bioinformatic tool. Finally, it was obtained a total of 7 679 031 and 7 854 922 for R. glutinis CON-5 with a GC% of 62 and 64%, and 6 770 404 forward and reverse sequences for R. kratochvilovae POR-3 with a GC percentage of 61%. These genome data represent the starting material for assembly of the sequences to obtain the complete genome of the strains and their subsequent analysis.